The Influence Of Workload And Resilience On Work Productivity For Employees In Bandar Lampung City - Fita Hidayatul Insani; Reniza Helena Putri (Jurnal Ekonomi, 2024)
In the era of globalization, work productivity is crucial to remain competitive. The increase in employee productivity across various sectors has become very important in Bandar Lampung, a rapidly growing economic center. While employee resilience is crucial in managing suboptimal workloads, developing resilience can be an effective strategy for enhancing overall productivity. Using a quantitative method, this research investigates the relationship between work productivity, resilience, and employee workload in Bandar Lampung. The sample participants were aged between 20 and 40 years, reflecting the productive age group in the region. The survey method is used by sending questionnaires to respondents to collect relevant data. The results of the statistical tests explain the impact of workload and resilience on employee productivity levels. Statistical analysis shows a significant positive effect of workload, and resilience has been proven to have a strong impact in helping employees manage pressure in the workplace. Statistical analysis shows the t value of 2.099 for the workload variable partially> t table, which is 1.65536 with a significance level of 0.038 for the Workload variable smaller than 0.05. partially tested resilience variable has a t value of 60.612 greater than the t table value of 1.65536 with a significance level of 0.000 <0.05. Furthermore, simultaneous testing shows that both factors, namely workload and mental endurance, simultaneously play a substantial role in the increase of work productivity. This finding emphasizes the importance of paying attention to both aspects in the effort to optimize employee productivity in a dynamic work environment and provides an in-depth explanation of the workload in Bandar Lampung, as well as how to enhance employee resilience to encourage sustainable productivity improvement.